Risk factors associated with abnormal glucose tolerance in the early postpartum period among Japanese women with gestational diabetes. Issue 1 (4th December 2014) - Kugishima, Yukari; Yasuhi, Ichiro; Yamashita, Hiroshi; Fukuda, Masashi; Kuzume, Akiko; Sugimi, So; Umezaki, Yasushi; Suga, Sachie; Kusuda, Nobuko
Abstract: Objective: To identify the risk factors associated with abnormal glucose tolerance (AGT) on the first postpartum oral glucose tolerance test (OGTT) among Japanese women with gestational diabetes (GDM). Methods: In a retrospective study, data were analyzed from women with GDM who underwent their first postpartum OGTT 6–8 weeks post partum at a center in Omura, Japan, between January 1, 2007, and December 31, 2011. Women with diabetes or impaired glucose tolerance were deemed to have postpartum AGT. The association between postpartum AGT and various risk factors was analyzed. Results: Among 169 women who underwent a postpartum OGTT, 58 (34.3%) had AGT. The significant risk factors associated with postpartum AGT in univariate analysis were pre‐pregnancy body mass index ( P = 0.096), 1‐hour plasma glucose ( P = 0.006), hemoglobin A1c ( P < 0.001), insulinogenic index ( P = 0.05), an insulinogenic index of less than 0.4 ( P = 0.006), and insulin therapy during pregnancy ( P < 0.001). Independent risk factors identified by multivariate logistic regression models were insulinogenic index (odds ratio [OR] 0.10, 95% confidence interval [CI] 0.01–0.74; P = 0.002), an insulinogenic index of less than 0.4 (OR 5.70, 95% CI 1.69–21.66; P = 0.005), and insulin therapy during pregnancy (OR 3.43, 95% CI 1.03–12.55; P = 0.044). Conclusion: Among Japanese women with GDM, a lower insulinogenic index and use of insulin therapy during pregnancy are associated with early postpartum AGT.